15th Asia-Oceania Congress of Endocrinology (AOCE 2014) POSTER PRESENTATION ABSTRACTS - Poster Presentors (AOCE 2014) (Journal of the ASEAN Federation of Endocrine Societies, 2014)
The Organizing Committee of the 15th Asia Oceania Congress of Endocrinology (AOCE 2014) takes pride in submitting to the Journal of the ASEAN Federation of Endocrine Societies (JAFES) the research abstracts that were presented during the congress.